Resepsi Remaja Terhadap Dampak Pergaulan Bebas Di Dalam Film Dua Garis Biru - Rafly Pratama; Mahardiansyah Suhadi; Rifky Anindiya Yusuf (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2021)
The film is one of the mass communication media which has a big influence on society at large. a film is also a form of a message consisting of various symbols and signs that form a meaning system so that it can be interpreted by each person differently, depending on the person's reference and ability to grasp the meaning conveyed. The film Dua Lines Biru by Gina S. Noer takes the theme of teenage pregnancy in promiscuity. The interpretation of the conflict in this film scene becomes the background for the research to see the reception of the audience or the public in watching the film Dua Garis Biru. The purpose of this study was to analyze the reception of adolescent audiences on the impact of promiscuity in the film Dua Garis Biru. This research uses a qualitative method with an analytical approach to encoding and decoding theory from Stuart Hall, which observes the audience's position on the meaning of a work. An understanding of the impact of promiscuity in the film Two Blue Lines. The results of this study the audience dominates the Hemegony Position which means the message is conveyed and the audience accepts the meaning or message as it is. But several scenes are in the Negotiated Position and Oppositional Position because the informant has its own alternative meaning or reference in certain scenes.